Modelling and Analysis of Dynamics Characteristics of Face-gear Transmission System Considering Multi-state Engagement - Zhu Lingyun; Gu Meihua; Gou Xiangfeng (Jixie chuandong)
The dynamic characteristics of face-gear transmission system directly affect the stability and reliability of the equipment. In order to reveal the dynamics and dynamic characteristics of face-gear in the transmission process, a nonlinear dynamic model of bending, torsion and pendulum of face-gear transmission system considering multi-state engagement is established. The changes of the load distribution rate and dynamic meshing force in three engaging states are calculated numerically. Three different Poincaré maps are defined, and the influence of load on the engaging force and dynamic characteristics of the system is analyzed by combining bifurcation diagram, maximum Lyapunov exponent spectrum, phase diagram and time history diagram of dynamic engaging force. The results show that with the change of parameters and the occurrence of single and double teeth alternate engagement, complex phenomena such as disengagement, tooth surface engagement and tooth back contact will occur in the process of face-gear transmission. The research can provide a theoretical basis for improving the smoothness of face-gear transmission process.